AB0812 IS THE VISCERAL ADIPOSITY INDEX ASSOCIATED WITH THE PRESENCE OF CARDIOVASCULAR RISK SCORES AND COMORBIDITY IN PSORIATIC DISEASE?. (13th June 2020) - Omma, A.; Erden, F.; Colak, S.; Can Sandikci, S.; Omma, T.; Kasim, I.; Ozkara, A.; Erden, A.
Abstract : Background: Psoriatic disease (PsD) is a chronic immune-mediated inflammatory disorder and predominantly involves the skin and joints. There is a better known relationship between the severity of PsD with some comorbidities such as metabolic syndrome, cardiovascular disease and obesity. Visceral Adiposity Index (VAI) has been shown to be an important marker, gender- dependent for insulin resistance, adipose tissue function and distribution. Objectives: The aim of this study was to evaluate the relationship between the VAI and cardiovascular risk scores of patients with psoriatic arthritis. Methods: This study was conducted with 101 PsD patients who fulfilled the classification criteria for Psoriatic Arthritis (CASPAR) criteria and 98 healthy subjects. Demographic and clinical data were recorded. Disease activity was evaluated with the Health Assessment Questionnaire (HAQ), Disease Activity Index for Psoriatic Arthritis (DAPSA), Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), Bath Ankylosing Spondylitis Disease Activity Index (BASFI) and Psoriasis Area Severity Index (PASI). The SCORE, Framingham index, metabolic syndrome (MetS), Body mass index (BMI) and VAI values of the patients and the VAI values of the healthy subjects were calculated. Results: Mean BMI (kg/m 2 ) was calculated as 29.63 5.66. According to the SCORE measurements, 53 (52.5%) patients were at low risk, 45 (44.6 %) at moderate risk, and 3 (3 %) at high risk. No patients were at very high risk. According to the Framingham score, 72 patients (71.3%) were at low risk, 22 patients (21.8%) at intermediate risk and 7 patients (6.9%) at high risk. The risk was found to be statistically significantly higher in the PsD group compared to the healthy control group in respect of metabolic syndrome, obesity (BMI >30) and VAI levels (p<0.05). Significantly higher VAI levels were determined in PsD patients with metabolic syndrome, BMI> 30 (obesity), diabetes mellitus and hypertension compared to without these comorbidities (p<0.05). A statistically significant correlation was determined between low and moderate risk Framingham score, and the VAI levels of PsD patients. Correlations were determined between disease activity and metabolic and cardiovascular risks of patients. A weak correlation was observed between VAI levels and the Framingham score (Table). Conclusion: Patients with psoriasis are more susceptible to obesity and other diseases such as metabolic syndrome, dyslipidemia, cardiovascular diseases, insulin resistance and diabetes. Therefore, control of bodyweight in PsD patients is important for management of the disease. Since VAI can be calculated simply from routinely taken measurements, the VAI level can be used to determine cardiovascular risk and VAI may also provide clues about comorbidities in patients with newly diagnosed PsD. Disclosure of Interests: None declared